Reactive Oxygen Species and Mitochondrial Dynamics: The Yin and Yang of Mitochondrial Dysfunction and Cancer Progression - Jan Ježek; Katrina F. Cooper; Randy Strich (MDPI AG, 2018)
Mitochondria are organelles with a highly dynamic ultrastructure maintained by a delicate equilibrium between its fission and fusion rates. Understanding the factors influencing this balance is important as perturbations to mitochondrial dynamics can result in pathological states. As a terminal site of nutrient oxidation for the cell, mitochondrial powerhouses harness energy in the form of ATP in a process driven by the electron transport chain. Contemporaneously, electrons translocated within the electron transport chain undergo spontaneous side reactions with oxygen, giving rise to superoxide and a variety of other downstream reactive oxygen species (ROS). Mitochondrially-derived ROS can mediate redox signaling or, in excess, cause cell injury and even cell death. Recent evidence suggests that mitochondrial ultrastructure is tightly coupled to ROS generation depending on the physiological status of the cell. Yet, the mechanism by which changes in mitochondrial shape modulate mitochondrial function and redox homeostasis is less clear. Aberrant mitochondrial morphology may lead to enhanced ROS formation, which, in turn, may deteriorate mitochondrial health and further exacerbate oxidative stress in a self-perpetuating vicious cycle. Here, we review the latest findings on the intricate relationship between mitochondrial dynamics and ROS production, focusing mainly on its role in malignant disease.